Role of Songs when Teaching English within Inclusive Education - I. S. Samokhin; N. L. Sokolova; E. A. Mrachenko; M. G. Sergeyeva; M. V. Mishatkina (Научный диалог)
The subject of this research is the peculiarities of the use of musical works in teaching English. The review of modern scientific literature devoted to appeal to English-language songs in the school education is made. In the practical part the authors’ technique is described, tested in a number of Moscow universities, which, according to the authors, can be applied also at lower levels of the educational vertical. This method has two main functions: educational, involving students knowing the history of the well-known musical works and their verbal component, and hedonistic associated with the awakening of students’ positive emotions. The relevance of the chosen topic is determined by the implementation of the Federal law “On education in Russian Federation,” providing the use of inclusive techniques and technologies in learning and education. The novelty of the research is seen in the fact that a hedonic function of the educational environment is recognized not only as supporting the educational one, but also valuable in itself, having independent significance. The authors believe that educators should consider the use of song material as an auxiliary teaching method, not aspiring to a leading role, even within the individual classes.